Effects of Epithelial IL-13Rα2 Expression in Inflammatory Bowel Disease - Verstockt, Bram; Perrier, Clémentine; De Hertogh, Gert; Cremer, Jonathan; Creyns, Brecht; Van Assche, Gert; Ferrante, Marc; Ceuppens, Jan L.; Vermeire, Séverine; Breynaert, Christine (Frontiers in Immunology, 2018)
Background: Mucosal IL-13 Receptor alpha 2 (IL13RA2) mRNA expression is one of the best predictive markers for primary non-responsiveness to infliximab therapy in patients with inflammatory bowel disease (IBD). The objective of this study was to understand how IL-13Rα2, a negative regulator of IL-13 signaling, can contribute to IBD pathology. Methods: IL13RA2 knockout (KO) and wild type (WT) mice were exposed to dextran sodium sulfate (DSS) in drinking water to induce colitis. Furthermore, mucosal biopsies of healthy individuals and IBD patients before the start of anti-TNF therapy were obtained for immunohistochemistry and gene expression analysis. Results: After induction of DSS colitis, IL13RA2 KO mice had similar disease severity, but recovered more rapidly than WT animals. Goblet cell numbers and mucosal architecture were also more rapidly restored in IL13RA2 KO mice. In mucosal biopsies of active IBD patients, immunohistochemistry revealed that IL-13Rα2 protein was highly expressed in epithelial cells, while expression was restricted to goblet cells in healthy controls. Mucosal IL13RA2 mRNA negatively correlated with mRNA of several goblet cell-specific genes and with goblet cell numbers. Conclusions: The data suggest that IL-13Rα2 on epithelial cells contributes to IBD pathology by negatively influencing goblet cell recovery, goblet cell function and epithelial restoration after injury. Therefore, blocking IL-13Rα2 could be a promising agent for restoration of the epithelial barrier in IBD.